2022
DOI: 10.3389/fsufs.2022.1076364
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and impact of cassava brown streak and cassava mosaic diseases in Africa: A review

Abstract: Africa produces over half of global cassava; however, the continent's average yield is below the potential yields achieved under experimental conditions. Many factors contributing to low yield include lack of quality varieties, poor soils, limited access to capital, competition for labor, as well as pests and diseases. Plant diseases are the major biotic constraints to cassava production and have caused considerable food insecurity in Africa. Although there has been some level of disease management which has c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Several authors have previously reported the existence of this virus disease in Gabon [7,12,13]. Moreover, this disease has already been reported in several Central African countries as the primary threat to cassava cultivation [11,31,32]. This viral disease is caused by a geminivirus transmitted by a vector, whitefly, belonging to the species Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) [31,33].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have previously reported the existence of this virus disease in Gabon [7,12,13]. Moreover, this disease has already been reported in several Central African countries as the primary threat to cassava cultivation [11,31,32]. This viral disease is caused by a geminivirus transmitted by a vector, whitefly, belonging to the species Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) [31,33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the papaya mealybug, a new crop pest in South Sudan, causes up to 91% yield losses of papaya, severely affecting the livelihoods of smallholder farmers in the country (CABI, 2021). The spread of cassava brown streak disease (CBSD) (Alicai et al, 2016) and the increasing prevalence of cassava mosaic disease (CMD) in South Sudan (Chikoti & Tembo, 2022) could be having a sizeable economic impact. Available data from East and Central Africa that encompasses South Sudan indicate that CBSD and CMD cause up to 70% and between 77% and 97% yield losses estimated at US$100 million and US$1.9-2.7 billion dollars per year (Chikoti & Tembo, 2022), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The spread of cassava brown streak disease (CBSD) (Alicai et al, 2016) and the increasing prevalence of cassava mosaic disease (CMD) in South Sudan (Chikoti & Tembo, 2022) could be having a sizeable economic impact. Available data from East and Central Africa that encompasses South Sudan indicate that CBSD and CMD cause up to 70% and between 77% and 97% yield losses estimated at US$100 million and US$1.9-2.7 billion dollars per year (Chikoti & Tembo, 2022), respectively. These example data point to the devasting effects of pests on crop production in South Sudan, which largely remain uncounted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms of CMD are characterized by leaf curling and distortion, mosaic patterns, yellowing, and stunting, which ultimately lead to reduced plant growth, lowered yields, or even complete loss of the crop. The disease is primarily spread through contaminated cuttings, although whitefly-borne infection can also occur in some regions (Cassava Mosaic Disease, n.d.;Fondong, 2017;Chikoti & Tembo, 2022;Uke et al, 2022;Hareesh et al, 2023;Sheat & Winter, 2023). The severity of CMD varies across different regions and years.…”
Section: Introductionmentioning
confidence: 99%